Copycat crime among non-incarcerated adults. Issue 1 (2nd January 2020) - Surette, Ray; Chadee, Derek
ABSTRACT: With the emergence of copycat crime as a criminal justice concern, its prevalence is of current interest. This study estimates copycat crime's prevalence among an adult non-incarcerated population. Face-to-face guided interviews were conducted with 601 respondents with measures of copycat crime consideration and attempts collected. Comparisons with prior copycat crime estimates and exploratory correlational and logistic regression analyses were conducted. The results show that the prevalence of copycat crime among non-incarcerated adults was significant but substantially lower than levels previously reported for incarcerated populations. About 1 in 10 non-incarcerated general population adults reported having considered committing a copycat crime and 1 in 20 reported having attempted one. Similar to prior research findings, females were significantly less likely than males to report copycat crime histories. Age was also predictive for copycat attempts, and prior victimisation and new media use were predictive for copycat crime consideration. Policy implications are discussed and the need for continued research into the dynamics of copycat crime across cultures and gender is indicated.